Dedications in the Books and Journals Edited by Nikolai Novikov - Кочеткова, Наталья (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
Many of the numerous books and journals edited by Nikolai Novikov bear dedications. These paratexts can be very different, depending on the addressee and the author’s relation to the particular person: Catherine II, powerful patrons, curators of the Moscow University or its students, friends and like-minded acquaintances, women, etc. Certain journals are even dedicated to the Fatherland. Novikov’s dedications also differ in form: some of them are very short, others have the form of a letter. Novikov followed tradition but also often went beyond the Russian publishing practices of his epoch.